Identification of the Oleosin Genes and Functional Analysis of CeOle4 Gene in Cyperus esculentus L. - Yuanyuan Dong; Yuling Cui; Yijin Wang; Shiyu Luan; Xinyi Liu; Qi Yang; Weican Liu; Xiaowei Li; Nan Wang; Fawei Wang; Lei Gu; Ping Xue (Horticulturae)
Tiger nut is the tuber of the perennial herbaceous plant Cyperus esculentus L., whose unique underground tubers are not only the main reproductive organ but also an important oil storage site. Oleosin is the most abundant structural protein in the oil body, which is an important membrane structural protein, playing a role in the formation and stability of lipid droplets in oilseed crops. Most studies have focused on the oleosin in oilseeds, but rarely on the oil containing tuber. In this study, nine oleosin genes from the Cyperus esculentus transcriptome were identified and divided into two groups via phylogenetic analysis. The expression patterns of the nine oleosins were examined through quantitative real-time PCR (qRT-PCR) in various development stages of stem tissue (35 d, 50 d, 75 d, 90 d, and 120 d after sowing). The subcellular localization of CeOle4 indicated that this protein was localized exclusively to membrane, indicating that it functioned in the plasma membrane. The highly expressed gene CeOle4 within the CeOleosin gene family was further transformed into yeast cells and plant materials. The results demonstrate that CeOle4 can promote lipid synthesis, enhancing the stability of oil lipids at low temperature and changing seed phenotypic traits. This discovery addresses and enriches the research on the function of CeOleosin genes and lays the groundwork for future studies on novel and superior transgenic crops related to tiger nut.